Analisis Permasalahan Pelaku Usaha dalam Proses Pemenuhan Komitmen Registrasi Pangan Olahan Risiko Menengah Rendah - Ira Novianty Lestari; Raden Bayu Indradi; Nurul Wahyu Wadarsih (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Before processed food is marketed in Indonesia, business actors must register the food to obtain a distribution permit. For medium to low risk processed food, a distribution permit must be obtained by obtaining a Business Activity Support Business Permit (PB-UMKU) with a Certificate of Fulfillment of Processed Food Commitments. This article will discuss the difficulties faced by industry players in this process and explain the fulfillment of registration commitments for low-medium processed food. This research method is a literature search using a legislative approach in processing processed food registration, and to collect field research questions, a survey of business actors was carried out during the technical guidance activity "Fulfilling Commitments for Registration of Processed Food with Medium Low Risk". The results of the analysis show that there are three critical points that business actors need to pay attention to in the process of fulfilling commitments, namely suitability of product data, suitability of composition, and suitability of label design. Errors in selecting packaging due to non-compliance with the original packaging requirements provided are the most frequently encountered problems. Apart from that, business actors often do not upload important documents such as the Health Certificate/Free Sale Certificate, which is the main required document in the import product registration process. Other errors include selecting an incorrect food category, which results in non-compliance with applicable regulations and cancellation of registration commitments.